Pediatric Pancreatic Pseudocyst Associated With Cholelithiasis - Taha, Assad M. (1986)
Pseudocyst of the pancreas is an uncommon problem in pediatric practice, and when related to gallstones, it is rare. A 13-year-old male adolescent with pseudocyst of the pancreas associated with cholelithiasis and chronic cholecystitis presented with a peculiar clinical picture. The etiology, pathophysiology, diagnosis, and treatment of pancreatic pseudocysts and gallstone pancreatitis in children are discussed.